2019
DOI: 10.1248/bpb.b19-00174
|View full text |Cite
|
Sign up to set email alerts
|

Cinobufagin Promotes Cell Cycle Arrest and Apoptosis to Block Human Esophageal Squamous Cell Carcinoma Cells Growth <i>via</i> the p73 Signalling Pathway

Abstract: Cinobufagin isolated from traditional Chinese herbs has antitumour, anaesthetic, analgesic and antiinflammatory effects. Recently, the antitumour activity of cinobufagin has attracted increasing attention from researchers. However, the anticancer activity of this drug on esophageal cancer cells and the precise mechanism are unclear. In this study, we determined the inhibitory effect of cinobufagin on the growth of three esophageal squamous cell carcinoma cell lines and explored its underlying mechanism. EC-109… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Although cytotoxic side effects in cardiac myocytes by the administration of a high dose of cinobufagin contained in Chinese Medicine has been reported [37], emerging evidence has shown that cinobufagin effectively suppresses cancer growth and progression by inducing cell cycle arrest and apoptosis and inhibiting angiogenesis [38]. For example, cinobufagin was found to promote cell cycle arrest at the G2/M phase and apoptosis in hepatocellular carcinoma and esophageal squamous cell carcinoma by increasing the expression levels of pro-apoptotic p73 and BAX [39,40]. Cinobufagin was found to induce apoptosis in osteosarcoma cancer cells by suppressing cancer-promoting signaling pathways such as STAT3, Notch and NF-kB, and activating mitochondria-mediated apoptosis pathways [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Although cytotoxic side effects in cardiac myocytes by the administration of a high dose of cinobufagin contained in Chinese Medicine has been reported [37], emerging evidence has shown that cinobufagin effectively suppresses cancer growth and progression by inducing cell cycle arrest and apoptosis and inhibiting angiogenesis [38]. For example, cinobufagin was found to promote cell cycle arrest at the G2/M phase and apoptosis in hepatocellular carcinoma and esophageal squamous cell carcinoma by increasing the expression levels of pro-apoptotic p73 and BAX [39,40]. Cinobufagin was found to induce apoptosis in osteosarcoma cancer cells by suppressing cancer-promoting signaling pathways such as STAT3, Notch and NF-kB, and activating mitochondria-mediated apoptosis pathways [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, P16 is a good marker for acute injury, such as acute kidney injury, in which p16 plays a critical role not only in cellular senescence but also in inflammation, apoptosis, and the excessive accumulation of reactive oxygen species (ROS). A recent study indicated that cinobufagin could indirectly increase the expression of p21 to increase G2/M arrest [24], inducing cell apoptosis, which indicates that p21 functions in apoptosis as well as in cellular senescence. Consequently, here, we chose SA-b-GAL staining to define cellular senescence, which is widely accepted in senescent research as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs cause cell cycle arrest and induce apoptosis by increasing the expression of p21. Furthermore, some substances obtained from Chinese medicine have been shown to exert therapeutic effects on EC, which also proves the value of Chinese medicine in antitumor therapy (57).…”
Section: Resultsmentioning
confidence: 82%
“…Cinobufagin, isolated from traditional Chinese herbs, exerts antitumor, anesthetic, analgesic and anti-inflammatory effects. A previous study by Deng et al (57) indicated that cinobufagin induced ESCC cell cycle arrest at the G 2 /M phase and promoted apoptosis by regulating the expression of p21, indicating that traditional Chinese medicine may prove useful for the treatment of EC.…”
Section: Role Of P21 In the Treatment Of Esophageal Cancermentioning
confidence: 96%